Dėl priesagos -ynas vedinių kirčiavimo pietų aukštaičių ir rytų aukštaičių vilniškių šnektose - Lazauskaitė-Ragaišienė, Vilija (Baltistica, 2001)
ON THE ACCENTUATION OF THE DERIVATIVES WITH THE SUFFIX -ynas IN THE SOUTH AUKŠTAITISH AND EAST AUKŠTAITISH VILNIŠKIAI DIALECTSThe article deals with the phenomenon of variation between the 1st and the 3rd accentual classes in the group of derivatives with the suffix -ynas in the South Aukštaitish and East Aukštaitish Vilniškiai dialects of the Lithuanian language, e.g. alksnýnas 1/3 ‘alder scrubs’, beržýnas 1/3 ‘birch grove’, karklýnas 1/3 ‘osier-bed’. The dominance of the mobile accentual class in the group of derivatives under discussion could be explained on the basis of the accentuation of the basic substantives, the majority of which are characterized by the 3rd or the 4th, i.e. mobile, accentual class, e.g. kelmynaĩ‘stubby places’ (: kélmas 3 ‘stub’), pušynaĩ‘pine forests’ (: pušìs 4 ‘pine’). Some of the derivatives which are characterized by the mobile accentual class could be connected with the accentuation of the collective plural.
Keywords: dialektologija; akcentologija; priesaga -ynas